Effect of ultrasonic surface rolling process on microstructure and properties of hydride sintered pure titanium - YAO Jing; ZHANG Jiantao; LI Xingyi; LIU Zhongqiang; LIU Xiao; XIAO Zhiyu (Fenmo yejin jishu)
Surface hardening of the pure titanium sintered by titanium hydride was treated by ultrasonic surface rolling process (USRP) in this paper, and the effects of USRP on the microstructure evolution and properties of the hydride sintered pure titanium were investigated by X-ray diffraction (XRD), electron back scattering diffraction (EBSD), scanning electron microscope (SEM), and transmission electron microscope (TEM). The results demonstrate that a gradient microstructure is present after USRP with the static load of 600 N, the outermost layer of the deformed microstructure displays the equiaxial nanocrystals, and the average grain size of the fine grains is about 100 nm. As the distance from the surface increases, the crystal structure shows the massive crystal, lamellar structure, and equiaxed coarse crystal in turn, and the average thickness of the deformation layer is about 400 μm. The surface roughness, grain refinement, and high surface compressive residual stress caused by rolling synergistically help to form a dense and stable passive film on the deformation layer, which could improve the corrosion resistance effectively. In addition, taking advantages of the microstructure evolution, the ultimate tensile strength and yield strength are 640.57 MPa and 485.29 MPa, increased by 32.43% and 27.57%, respectively. Meanwhile, the surface hardness is increased by 36% for the USRP treated titanium alloy. However, the introduction of deformation layer leads to a decrease of uniform elongation, while the fracture morphology indicates a ductile failure.